PATHOGENETIC PREVENTION OF PROSTHETICS STOMATITIS IN PERSONS WITH INTERNAL DISEASES - Dvornyk, V.M.; Marchenko, A.V.; Ponomarenko, В.О.; Kovalenko, V.V.; Litovchenko, I.Yu.; Teslenko, O.I.; Jerys, L.B. (World of Medicine and Biology, 2022)
Primary and secondary prevention of prosthetic stomatitis in patients using removable dentures remains a topical and priority area of dentistry. The methods of prevention of chronic prosthetic stomatitis developed in the background of their internal diseases developed and tested by the authors of the article are effective, reduce the number of visits for prosthesis correction, are accessible and easy to perform for elderly and senile patients. They improve the adaptation of the oral mucosa to the basis of a removable prosthesis, adjust the general condition of the body and thus improve the quality of life of patients, as evidenced by the normalization of their psycho-emotional status. An individualized and differentiated approach to maintenance therapy prevents exacerbation of prosthetic stomatitis during the year in 78 % of patients.
Keywords: stomatitis; prevention; altan; thiotriazoline; biol; quertin